Cellular automata approach for modelling climate change impact on water resources - Kassogué, Hamidou; Bernoussi, Abdes Samed; Amharref, Mina; Ouardouz, Mustapha (International journal of parallel, emergent and distributed systems, 2019)
In this work, we consider the cellular automata (CA) approach for modelling the climate change impact on water resources. This consists in: constructing a CA model that describes the water cycle dynamics taking into account physical terrain attributes and climatic constraints; coupling the CA model with climate projection scenarios for a considered region as input data; determining and analysing in output the variations of the underground, surface and evaporated water. We present these variations per time interval and per zone of influence. As an application, we consider simulation for a basin in northern Morocco using a simulation software we have designed in Java Object Oriented Programming. We consider cellular automata (CA) approach for modelling climate change impact on water resources. This consists in, first constructing a CA model that describes the water cycle dynamics taking into account physical terrain attributes and climatic constraints, then coupling the CA model with climate projection scenarios for a considered region as input data, and we determine and analyze in output the variations of the water resources (groundwater and surface water). We present these variations per time interval and per zone of influence. The approach application is for a basin in northern Morocco for which we use simulation software that we have designed in Java Object Oriented Programming. Digital terrain model, geological map and satellites image are used for input data.